Experimental Study of PCM Cooling Storage System for Hot Climates (Future Cities and Environment, 2022)
In this work, the application of a PCM cooling system for hot climate applications is investigated. A novel design proposes the utilization of PCM panels to reduce the energy demand on an air-cooling system by absorbing a proportion of the thermal load. The system not only contemplates the application of the S27 PCM panels for indoor cooling but also considers a PCM-TES box to enhance the cooling performance. The experimental evaluation focused on two operating schedules, during daytime the environmental temperature was considered at 30°C, and at night-time, the temperature was reduced to 25°C. The results found an indoor average temperature difference of 1.8°C with the addition of the PCM panels. In terms of energy savings, the chiller energy consumption was positively impacted as the PCM reduced the operational time.